1996
DOI: 10.1037/0033-2909.120.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure and personality: A meta-analytic review.

Abstract: A meta-analysis of 295 relevant effect sizes obtained from 25,469 participants confirmed expectations that elevated blood pressure (BP) and essential hypertension (EH) would be associated with lower affect expression but with more negative affectivity and defensiveness. The strongest associations occurred for defensiveness and measures of anger and affect expression linked to an interpersonal context(s). However, a number of other factors also were found to moderate associations of BP with personality measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
149
3
6

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(164 citation statements)
references
References 191 publications
5
149
3
6
Order By: Relevance
“…In a sample of several thousand medical patients, for example, Schwartz, Krupp, and Byrne (1971) found that participants who minimized their conscious feelings of anxiety reported more organic problems, whereas those who focused on them reported more psychological problems. A recent meta-analysis found that defensive constriction of emotional experience was the best predictor of essential hypertension (elevated blood pressure of unknown origin) of any personality variable yet studied ( Jorgensen, Johnson, Kolodziej, & Schreer, 1996 ).…”
Section: Defense Against Unpleasant Emotions and Its Physiological Comentioning
confidence: 99%
“…In a sample of several thousand medical patients, for example, Schwartz, Krupp, and Byrne (1971) found that participants who minimized their conscious feelings of anxiety reported more organic problems, whereas those who focused on them reported more psychological problems. A recent meta-analysis found that defensive constriction of emotional experience was the best predictor of essential hypertension (elevated blood pressure of unknown origin) of any personality variable yet studied ( Jorgensen, Johnson, Kolodziej, & Schreer, 1996 ).…”
Section: Defense Against Unpleasant Emotions and Its Physiological Comentioning
confidence: 99%
“…A considerable number of studies (e.g., (Gallacher, Yarnell, Sweetnam, Elwood, & Stansfeld, 1999;Vögele, Jarvis, & Cheeseman, 1997;Vogele & Steptoe, 1992)) also demonstrated that inhibition of anger expression elevated cardiovascular reactions to stress while over anger expression did not. A meta-analysis of 295 relevant effect sizes from studies of suppression obtained from 25,469 participants (Jorgensen, Johnson, Kolodziej, & Schreer, 1996) found that lower affect expression (as well as defensiveness) was associated with higher BP and greater hypertension. …”
mentioning
confidence: 99%
“…Of these factors, individual differences in the experience and expression of various distressing emotional states-i.e., anger/hostility, depression, anxiety, and cynicism-are routinely discussed and have been found to be associated with numerous adverse health conditions, including coronary heart disease (Kubzansky & Kawachi, 2000;Suls & Bunde, 2005), high blood pressure (Jorgensen, Johnson, Kolodziej, & Schreer, 1996;Patten et al, 2009;Yan et al, 2003), asthma (Huovinen, Kaprio, & Koskenvuo, 2001;Lehrer, Isenberg, & Hochron, 1993;Loerbroks, Apfelbacher, Thayer, Debling, & Sturmer, 2009), stroke (Colantonio, Kasl, & Ostfeld, 1992;Everson, Roberts, Goldberg, & Kaplan, 1998), and diabetes (Anderson, Freedland, Clouse, & Lustman, 2001;Lustman, Frank, & McGill, 1991). However, the role and importance of positive emotions in health is less clear, although emerging evidence suggests that these emotions may serve as a protective factor against illnesses and mortality (Fredrickson, 1998;Pressman & Cohen, 2005;Richman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%